The Principal's Role in Creating a School Climate with Noble Moral Nuances during a Limited Face-to-Face Period - Sri Denti (Ruhama : Islamic Education Journal, 2022)
This study aims to determine the climate of Akhlak-nuanced schools at Semen Padang Private High School. How the principal's role during the face-to-face meeting period is limited. The results showed that: The moral school climate at Semen Padang Private High School is very pronounced every day starting from the process of arriving students in the morning, program 3 S (Smile, Greetings and Greetings), reading the Qur'an before the first class hour begins until the return of students back home in the afternoon. The Muhadharah (Bina Remaja Islam) program and infak every Friday, the commemoration of islamic holidays (PHBI) which are contained in the matriculation of religious programs at Semen Padang Private High School, as well as other school programs that are extracurricular in nature. The principal's role as managerial during face-to-face meetings is limited to managing educational personnel and continuing to carry out professional development by conducting In-House Training in establishing the Operational Curriculum of the Education Unit (KOSP). As an educator, the principal implements and demonstrates a high commitment to learning activities and ensures that the school climate runs well. As a supervisor, the principal continues to strive and communicate the role of all teachers, even parents, even during limited face-to-face meetings with strict health protocols.